Znaczenie wolontariatu w opiniach studentów pedagogiki - Turska, Elżbieta (Adult Education Discourses, 2020)
The aim of this paper is to identify, classify and present the importance of volunteering in the opinion of student volunteers. Materials and methods: The study consisted of two stages. In the first one a diagnostic poll with the use of a survey was carried out. 76 pedagogy student volunteers studying at the University of Zielona Góra took part in this stage. The second stage was based on case studies consisting of narrative interviews, this stage was completed by 12 students.Results: Four classes of importance of volunteering assigned by students have been identified in the study: 1. volunteering as a natural aspect of social interaction; 2. volunteering as a path to self-improvement; 3. volunteering as a way to overcome difficult life experiences; 4. volunteering as a wayto find a future career path.